2003
DOI: 10.1046/j.1365-246x.2003.01973.x
|View full text |Cite
|
Sign up to set email alerts
|

Joint inversion of local, regional and teleseismic data for crustal thickness in the Eurasia-Africa plate boundary region

Abstract: SUMMARY A new map for the Moho discontinuity (EAM02) in the Eurasia–Africa plate boundary region is presented. Reliable results have also been obtained for the southern and eastern Mediterranean Basin, the northern African coasts and the eastern Atlantic Ocean, regions only occasionally considered in studies on the Mediterranean region. The Moho topography model is derived from two independent sets of constraints. Information contained in the fundamental and higher‐mode Rayleigh waves obtained from waveform mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
79
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 87 publications
13
79
2
Order By: Relevance
“…The dip of each segment was adjusted following structural models of the forearc region that were derived from wide angle seismics (Bohnhoff et al, 2001;Brönner, 2003), surface wave and receiver function analysis (Li et al, 2003;Meier et al, 2004a;Endrun et al, 2004) and moving source profiles (Truffert et al, 1993). Furthermore, we implement data from a Moho map of the Eastern Mediterranean (Marone et al, 2003). We defined all events above the contact zone as brittle failure within the upper Aegean plate and all events below as earthquakes within the dipping African lithosphere.…”
Section: Data Base and Procedures Appliedmentioning
confidence: 99%
“…The dip of each segment was adjusted following structural models of the forearc region that were derived from wide angle seismics (Bohnhoff et al, 2001;Brönner, 2003), surface wave and receiver function analysis (Li et al, 2003;Meier et al, 2004a;Endrun et al, 2004) and moving source profiles (Truffert et al, 1993). Furthermore, we implement data from a Moho map of the Eastern Mediterranean (Marone et al, 2003). We defined all events above the contact zone as brittle failure within the upper Aegean plate and all events below as earthquakes within the dipping African lithosphere.…”
Section: Data Base and Procedures Appliedmentioning
confidence: 99%
“…The global maximum of the H-K stack for KSLM is at 37.4 km in thickness and 1.80 Vp/Vs ratio with 0.6 km (~1.6%) and 0.02 (~1.11%) uncertainties while the local maximum is at 31.8 km in thickness and 2.0 Vp/Vs ratio. While the study results of Marone et al (2003) showed that the crustal thickness near the KSLM station is almost 32 km, most previous studies (e.g., Arslan et al, 2010;Molinari and Morelli, 2011;Laske et al, 2013;Tezel et al, 2013;Vanacore et al, 2013;Uluocak et al, 2016) agreed with the crustal thickness at the global maximum. The H-K stack for SERE shows a significantly shallower Moho depth (31.4 km) and higher Vp/Vs ratio (1.87) at the local maximum than the findings of previous studies (e.g., Marone et al, 2003;Arslan et al, 2010;Molinari and Morelli, 2011;Laske et al, 2013;Tezel et al, 2013;Vanacore et al, 2013;Uluocak et al, 2016).…”
Section: Inversion Resultsmentioning
confidence: 79%
“…Some of them assert that the crustal thickness of the Anatolian plate gets thinner from east to west (e.g., Marone et al, 2003;Angus et al, 2005;Luccio and Pasyanos, 2007;Maden et al, 2008). Marone et al (2003) determined that the mean crustal thickness in Central Anatolia varies between 36 and 40 km. Arslan et al (2010) studied the crustal structure of Turkey using gravity data and found results very similar to those of Marone et al (2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by the relative low Pn velocity of 7.7-7.9 km/s. Additional information has been recently obtained by receiver function studies of Sandvol et al (1998) and Van der Meijde et al (2003). The results of Van der Meijde et al (2003) show that the Mohorovicic (Moho) discontinuity under Midelt (in the plains north of the High Atlas) is located at 39 km.…”
Section: Seismic Refraction Studiesmentioning
confidence: 95%